DNA barcoding inferred maternal philopatric affinity of ocean maskray (Neotrygon indica) in the Bay of Bengal - Shantanu Kundu; Kaomud Tyagi; Swarup Ranjan Mohanty; Sanmitra Roy; Anil Mohapatra; Vikas Kumar; Kailash Chandra (Mitochondrial DNA. Part B. Resources, 2019)
The Indian Ocean maskray, Neotrygon indica, is a recently described species from the Bay of Bengal in the eastern coast of India. The conspicuous morphology and less genetic information of this group are often confusing for their identity and phylogeography. In this study, we have collected the specimens from Odisha coast in eastern India and generated the DNA barcode data for comparative analysis with publicly available barcodes of N. indica and other congeners. The morphological characters are similar to the previous record of N. indica. However, the generated barcode data of N. indica showed 2.2–8.0% inter-species genetic distances with the other six species. The studied population of N. indica showed 0.2–1.5% genetic distances with a different known population (Tamil Nadu, Andhra Pradesh, and Bangladesh) in the Bay of Bengal. The BA phylogeny revealed monophyletic clustering of all the studied species. Henceforth, the shallow genetic divergences within the different population of N. indica depicted possible female precise natal philopatric affinity within their range distribution. To corroborate this unique phylogeographic structure, this study evoked more rigorous sampling and detailing with other molecular markers. This study also exhibits the expand range distribution of N. indica beyond its type locality and furnishes a new state record for Odisha. Our data would be a valuable resource for further studies on genetic diversity of N. indica and related species, which will provide new insights for better conservation plans.